2014
DOI: 10.1002/ejoc.201403062
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of C‐2‐Methylene and C‐2‐Methyl α‐ and β‐C‐Glycosides from 2‐C‐Branched Glycals: Formal Total Synthesis of (–)‐Brevisamide

Abstract: The stereoselective synthesis of deoxy C‐glycoside derivatives that have a methylene or methyl group at C‐2 position was investigated by employing the Claisen rearrangement of 2‐vinyloxy methyldeoxy‐glycals as the synthetic precursors. The method proceeded with high diastereoselectivity to afford C‐2‐methylene α‐C‐glycosides. Complementary to this protocol, a ZnII‐mediated anomerization of the α‐C‐glycosides to give the corresponding β‐C‐glycosides was also used to obtain diastereomerically pure C‐2‐methylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The same approach was used by Sridhar and co-workers, who reported that hydrogenation of exo -olefin 17 using Pd/C and Na 2 CO 3 proceeded from the sterically less hindered equatorial face to afford the axial methyl isomer 18 with a diastereomeric ratio of 75:25 (Scheme ). We initially expected that olefin 14 would be fixed in the chair conformation by the trans -decalin-like bicyclic system and would therefore afford better axial-methyl selectivity than the monocyclic system 17 during catalytic hydrogenation. The hydrogenation of 14 , however, showed low diastereoselectivity when using Pd­(OH) 2 or RhCl­(PPh 3 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same approach was used by Sridhar and co-workers, who reported that hydrogenation of exo -olefin 17 using Pd/C and Na 2 CO 3 proceeded from the sterically less hindered equatorial face to afford the axial methyl isomer 18 with a diastereomeric ratio of 75:25 (Scheme ). We initially expected that olefin 14 would be fixed in the chair conformation by the trans -decalin-like bicyclic system and would therefore afford better axial-methyl selectivity than the monocyclic system 17 during catalytic hydrogenation. The hydrogenation of 14 , however, showed low diastereoselectivity when using Pd­(OH) 2 or RhCl­(PPh 3 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This molecule has a hybrid structure comprising the A ring of brevenal and brevisin, including the 3,4-dimethylhepta-2,4-dienal side chain, and the A ring of the tamulamides, possessing an acetamide side chain. This unique biosynthetic product has attracted the attention of organic chemists, and seven total ,,,,, and six formal ,,, syntheses have appeared in the literature since the first report by Satake and Tachibana in 2009 . An overview of these synthetic strategies is provided in Figure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vilsmeier-Haack (VH) one-step direct formylation of glycals has been the most sought after by numerous research groups worldwide. 19,20,21,22 Scheme 1: Synthesis of C-2-formyl glycals 2a-f.…”
Section: Vilsmeier Haack Formylationmentioning
confidence: 99%
“…Thus, thermal rearrangement of 2-vinyloxymethyl glucal 701 at 180 °C followed by reduction of the resulting aldehyde with NaBH 4 gave C -glycoside 702 (81%, α/β = 66:34) (Scheme ). Enol ether 703 was subjected to Claisen rearrangement, providing β- C -glycoside 704 in 84% yield. Disaccharide derivative 705 underwent thermal Claisen rearrangement to provide α-(1 → 6)-pseudo- C -disaccharide 706 in 83% yield …”
Section: Synthesis Of C-glycosides Through Rearrangement Of Sugar Pre...mentioning
confidence: 99%